2009
DOI: 10.1097/01.pra.0000358319.81307.a5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Olanzapine and Risperidone on Metabolic Factors in Children and Adolescents: A Retrospective Evaluation

Abstract: Inpatient treatment with both olanzapine and risperidone was correlated with a significant increase in BMI. Olanzapine also resulted in increased risk factors for diabetes and metabolic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…A study in children treated with risperidone and followed for 8 weeks found significant increases in body weight, BMI Z -scores and waist circumference, but no differences in plasma lipids or glucose. 19 Another study showed that children treated with olanzapine and risperidone and followed for 4 weeks had significant increases in BMI, but only those treated with olanzapine had elevations in blood pressure and diagnosis of MetS from baseline 20 suggesting the type of SGA-treatment may influence the development of MetS characteristics. However, in our current study only 3.8% of the children were treated with olanzapine, with the majority treated with either risperidone (43.8%) or quetiapine (46.7%), similar to our prior study.…”
Section: Discussionmentioning
confidence: 99%
“…A study in children treated with risperidone and followed for 8 weeks found significant increases in body weight, BMI Z -scores and waist circumference, but no differences in plasma lipids or glucose. 19 Another study showed that children treated with olanzapine and risperidone and followed for 4 weeks had significant increases in BMI, but only those treated with olanzapine had elevations in blood pressure and diagnosis of MetS from baseline 20 suggesting the type of SGA-treatment may influence the development of MetS characteristics. However, in our current study only 3.8% of the children were treated with olanzapine, with the majority treated with either risperidone (43.8%) or quetiapine (46.7%), similar to our prior study.…”
Section: Discussionmentioning
confidence: 99%
“…Khan reviewed the effects of olanzapine and risperidone on patients (mean age of 13) over a 27-day duration. They showed that the study group had a significant increase in Body Mass Index (BMI) for both medications with mean increases in weight being 9.1 lbs and 7.4 lbs, respectively [11]. Though the amount of weight gained varies with each SGA and may be person-specific, it is becoming clearer that weight gain in children and adolescents on SGAs is the trend and not the exception.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 20 PWS cases who were AP na€ ıve at admission and subsequently started an AP during their inpatient stay, 11 were matched exactly to 11 PWS controls according to age, sex, raceethnicity, genetic type, and IQ score. Age (yrs), sex, race-ethnicity, and genetic type were matched exactly, and IQ score was matched according to the following categories: no mental retardation (> 70), mild retardation (50-69), moderate retardation (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49), severe retardation (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), and profound retardation (< 20). These cases and controls could be matched on genetic type and IQ score in addition to age, sex, and race-ethnicity due to the large difference in sample size between the cases (n=11) and pool of controls (n=338).…”
Section: Methodsmentioning
confidence: 99%
“…There is a well‐documented association between AP use and the development of rapid and extensive weight gain in the general population . Several mechanisms have been postulated for the associated weight gain, including blockade of the serotonin 5‐HT 2C and histamine H 1 receptors, antagonism of dopamine and norepinephrine at the hypothalamus (affecting satiety), and changes in leptin, prolactin, cytokines, reproductive hormones, and cortisol levels . Although previous research has shown that some of the newer, second‐generation APs (SGAs) result in more weight gain than certain older, first‐generation APs (FGAs), recent evidence suggests that the risk for weight gain and metabolic complications is not class specific and varies within each class .…”
mentioning
confidence: 99%
See 1 more Smart Citation